Analysis of Production, Impact, and Scientific Collaboration on Difficult Airway Through the Web of Science and Scopus (1981–2013) - García-Aroca, Miguel Ángel; Pandiella-Dominique, Andrés; Navarro-Suay, Ricardo; Alonso-Arroyo, Adolfo; Granda-Orive, José Ignacio; Anguita-Rodríguez, Francisco; López-García, Andrés (Anesthesia and analgesia, 2017)
Bibliometrics, the statistical analysis of written publications, is an increasingly popular approach to the assessment of scientific activity. Bibliometrics allows researchers to assess the impact of a field, or research area, and has been used to make decisions regarding research funding. Through bibliometric analysis, we hypothesized that a bibliometric analysis of difficult airway research would demonstrate a growth in authors and articles over time. Using the Web of Science (WoS) and Scopus databases, we conducted a search of published manuscripts on the difficult airway from January 1981 to December 2013. After removal of duplicates, we identified 2412 articles. We then analyzed the articles as a group to assess indicators of productivity, collaboration, and impact over this time period. We found an increase in productivity over the study period, with 37 manuscripts published between 1981 and 1990, and 1268 between 2001 and 2010 (P < .001). The difficult airway papers growth rate was bigger than that of anesthesiology research in general, with CAGR (cumulative average growth rate) since 1999 for difficult airway >9% for both WoS and Scopus, and CAGR for anesthesiology as a whole =0.64% in WoS, and =3.30% in Scopus. Furthermore, we found a positive correlation between the number of papers published per author and the number of coauthored manuscripts (P < .001). We also found an increase in the number of coauthored manuscripts, in international cooperation between institutions, and in the number of citations for each manuscript. For any author, we also identified a positive relationship between the number of citations per manuscript and the number of papers published (P < .001). We found a greater increase over time in the number of difficult airway manuscripts than for anesthesiology research overall. We found that collaboration between authors increases their impact, and that an increase in collaboration increases citation rates. Publishing in English and in certain journals, and collaborating with certain authors and institutions, increases the visibility of manuscripts published on this subject.